1999
DOI: 10.1152/ajprenal.1999.276.5.f666
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the polymeric immunoglobulin receptor and excretion of secretory IgA in the postischemic kidney

Abstract: The humoral mucosal immune response of the kidney involves the transport of secretory IgA (S-IgA) through renal epithelial cells by the polymeric immunoglobulin receptor (pIgR). The pIgR is cleaved and released as free secretory component (FSC) or attached to IgA (S-IgA). We examined the effects of an ischemic model of acute renal failure (ARF) on the expression of pIgR and the secretion of FSC and S-IgA in the urine. Kidney pIgR mRNA levels decreased in ischemic animals by 55% at 4 h and by 85% at 72 h compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…We reported decreased pIgR mRNA and protein levels in the kidney in other models of renal stress compared with control, including water-loading (11) and ischemia-reperfusion injury (12). As several factors have been reported to increase transcription of the pIgR, including glucocorticoids (37) and proinflammatory cytokines (38), and E. coli bacterial infection increases cytokines (39) that are known to increase pIgR expression (8,40), we expected to see an increase in pIgR expression in the kidney in our ascending pyelonephritis model.…”
Section: Regulation Of Pigr Rna and Protein Expression In The Kidney mentioning
confidence: 97%
See 1 more Smart Citation
“…We reported decreased pIgR mRNA and protein levels in the kidney in other models of renal stress compared with control, including water-loading (11) and ischemia-reperfusion injury (12). As several factors have been reported to increase transcription of the pIgR, including glucocorticoids (37) and proinflammatory cytokines (38), and E. coli bacterial infection increases cytokines (39) that are known to increase pIgR expression (8,40), we expected to see an increase in pIgR expression in the kidney in our ascending pyelonephritis model.…”
Section: Regulation Of Pigr Rna and Protein Expression In The Kidney mentioning
confidence: 97%
“…We have demonstrated that pIgR mRNA levels and pIgR protein levels are decreased in the rat kidney by renal ischemia (12). The significance of decreased pIgR protein levels induced by ischemia in the mucosal defense of the kidney is suggested by the frequent association of UTI with acute renal failure (13) and with the early (postischemic) renal transplant period (14).…”
mentioning
confidence: 97%
“…dIgA is typically produced by plasma cells located in the lamina propria, near the basolateral surface of mucosal epithelia. pIgR has been found in mouse and rat kidney tubule epithelial cells (19), and pIgR expression can be regulated by water deprivation, vasopressin administration, or renal ischemia-reperfusion in rats (20,21). dIgA can be found in urine, suggesting that it can reach the urinary space by pIgR-mediated transcytosis (21).…”
mentioning
confidence: 99%
“…pIgR has been found in mouse and rat kidney tubule epithelial cells (19), and pIgR expression can be regulated by water deprivation, vasopressin administration, or renal ischemia-reperfusion in rats (20,21). dIgA can be found in urine, suggesting that it can reach the urinary space by pIgR-mediated transcytosis (21). pIgR expression has been shown to be regulated by IL-4, TNF-␣, and IFN-␥ in airway, intestinal, and mammary gland epithelial cells (22), and a STAT6 binding domain has been identified in intron 1 of the pIgR gene (23,24).…”
mentioning
confidence: 99%
“…82,83 One study that investigated the tubular expression of secretory component failed to demonstrate positivity for this receptor in rat glomeruli. 84 Human specimens have not yet been investigated carefully.…”
Section: Secretory Componentmentioning
confidence: 99%